Robotic Virtue, Military Ethics Education, and the Need for Proper Storytellers - Syse, Henrik; Cook, Martin (Conatus - Journal of Philosophy, 2023)
The introduction of artificial intelligence (AI) challenges much of our traditional understanding of military ethics. What virtues and what sort of ethics education are needed as we move into an ever more AI-driven military reality? In this article we suggest and discuss key virtues that are needed, including the virtue of prudence and the accompanying virtue of good and proper storytelling. We also reflect on the ideal of “explainable AI,” and philosophize about the role of fear in helping us understand what is actually at stake in a military infused with AI-enabled and AI-driven weapons.